Analysis vibration and detect the cracks in the FGM by XFEM and WAVELET - Chương Thiết Tú,; Hoàng Trung Hiền,; Trần Thị Trà Mi,; Lâm Phát Thuận,; Nguyễn Hoài Sơn, (Journal of Technical Education Science, 2013)
In fracture mechanics, crack identification is an important issue but it’s not easy to carry out, crack identification can detect by ultrasonic, diffraction method and so on. When a structure has a crack, the dynamic characteristics of the structure, such as natural frequencies and mode shapes, will be changed. In this paper, a method based on the wavelet analysis of modal vibration data is introduced to detect the cracks in the Functionally Graded Material (FGM) plate based on analyzing free vibration of a FGM plate by wavelet analysis. In practice, the modal vibration data which include the natural frequencies and mode shapes of cracked plate are usually defined by measured equipments, measurement data of free vibration will be processed by Wavelet to detect the crack of plate…. In this research, the two-dimensional wavelet transform to analysis vibration signal. The numerical results show that the proposed method is not only accurate but also relatively visual.